Association of human papilloma virus status and response to radiotherapy in vulvar squamous cell carcinoma. Issue 1 (25th November 2019) - Proctor, Lily; Hoang, Lien; Moore, Jocelyn; Thompson, Emily; Leung, Samuel; Natesan, Divya; Chino, Junzo; Gilks, Blake; McAlpine, Jessica N
Abstract : Introduction: Vulvar squamous cell carcinoma develops through two separate pathways, associated with the presence or absence of high-risk human papilloma virus (HPV). The objective of this study was to evaluate treatment response and clinical outcomes in women with HPV-associated versus HPV-independent vulvar squamous cell carcinoma treated with primary radiation therapy, in order to determine the ability to use HPV status as a predictor of response to radiation therapy. Methods: This was a retrospective cohort study combining data from British Columbia Cancer, Canada and Duke University, USA. Patients were included who had been treated with radiation therapy but excluded if they had received major surgical interventions. Immunohistochemistry for p16 (as a surrogate for high-risk HPV infection) and p53 was performed. We analyzed the univariable association between p16 status and clinico-pathological features and performed univariable survival analysis for p16. Results: Forty-eight patients with vulvar squamous cell carcinoma treated with primary radiation therapy were identified: 26 p16 positive/HPV-associated patients and 22 p16 negative/HPV-independent patients. p16 positive vulvar squamous cell carcinoma demonstrated a significantly improved overall survival (HR 0.39, p=0.03) and progression-free survival (HR 0.35, p=0.02). In women treated with definitive radiation therapy, p16 positivity was associated with improved overall survival (HR 0.29, p<0.01) and progression-free survival (HR 0.21, p<0.01). Among patients who received sensitizing chemotherapy, a significant association was observed with p16 positive tumors and overall survival (HR 0.25, p=0.03) and progression-free survival (HR 0.09, p<0.01). Conclusion: This study suggests that HPV status in vulvar squamous cell carcinoma has both prognostic and predictive implications, with increased radiosensitivity demonstrated in HPV-associated vulvar squamous cell carcinoma. Implications may include radiation dose de-escalation for HPV-associated vulvar squamous cell carcinoma and increased surgical aggressiveness for HPV-independent vulvar squamous cell carcinoma.